Anti-icing-deicing composite surface and preparation method thereof
By coupling superhydrophobic/lubricating fluid and hydrophobic/lubricating fluid microstructures on the porous material substrate, the superhydrophobic and superslip characteristics of the anti-ice-ice composite surface are achieved, and the ice adhesion and the ice adhesion in the prior art are solved. The problem of lubricating fluid loss significantly improves the surface's ice removal performance and service life.
Patent Information
- Application Number
- CN202411554907.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The existing superhydrophobic surfaces are difficult to remove ice after freezing, while the superslip surface has a short service life due to the easy loss of lubricating fluid, which cannot effectively solve the problems of ice adhesion and lubricating fluid loss.
Using an anti-ice-scattering composite surface, the superhydrophobic/lubrication fluid and hydrophobic/lubrication fluid are coupled on the porous material substrate, and the superhydrophobic/lubrication fluid is not infiltrated by the lubricating fluid, while the hydrophobic fluid is used. /The lubricating fluid is completely wrapped by the lubricating fluid, achieving the surface with both superhydrophobic and superslip characteristics.
After freezing, this surface can greatly reduce the adhesion of ice, making ice easier to remove, and at the same time extend the service life of the surface, effectively solving the problems of ice adhesion and lubricating fluid loss in the prior art.
Smart Images

Figure CN119408715A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of anti-icing and ice-repelling, and in particular relates to an anti-icing-ice-repelling composite surface and a preparation method thereof. Background Art
[0002] Icing is very common in life, but it can cause great safety problems in the fields of aviation and navigation. For example, ice on the wings at high altitudes can cause aircraft stalls and aviation accidents, and ice on ocean-going cargo ships can affect normal navigation. A superhydrophobic surface is a surface with good hydrophobicity. The contact angle of water droplets on its surface can reach more than 150°, and the contact angle hysteresis is less than 10°. Due to its good hydrophobicity, this surface can make water droplets roll off quickly after falling on the surface. Therefore, in the fields of aviation and navigation, this surface is also used to prevent ice on the surface of equipment. However, to achieve good superhydrophobic properties, microstructures and low surface energy are indispensable. This also means that when the superhydrophobic surface is used for anti-icing, once the surface is damaged, water droplets will adhere to the superhydrophobic surface and freeze. During the freezing process, ice crystals will be embedded in the microstructure of the superhydrophobic surface, forming a strong bond similar to a mortise and tenon structure, making the resulting ice very difficult to remove.
[0003] Inspired by surfaces such as pitcher plants, scholars have proposed a super-slippery surface with lubricating fluid injection. A super-slippery surface is a surface covered with a lubricating fluid that is prepared by injecting a lubricating fluid into the surface of a solid material. With the help of the lubricating fluid on its surface, the super-slippery surface transforms the contact between the solid material and water into the contact between the lubricating fluid and water, thereby greatly reducing the adhesion of water on the solid surface. This will make it easier for water to fall off the surface of the material after freezing, and the lubricating oil film on the super-slippery surface also reduces the thermal conductivity between the solid surface and water, further delaying freezing. However, because water droplets are not easy to fall off after falling on the super-slippery surface, it is easier for the surface to form large areas of ice. A large amount of lubricating oil will be taken away in the process of ice shedding. This greatly reduces the service life of the super-slippery surface.
[0004] It can be seen that both super-hydrophobic surfaces and super-slippery surfaces have their own fatal shortcomings in the field of anti-icing. In the current research on super-slippery surface anti-icing, various bionic structure super-hydrophobic coatings and super-hydrophobic anti-icing surfaces have been disclosed to basically solve the problems of poor wear resistance of super-hydrophobic materials and poor life of super-hydrophobic surfaces, but none of them mention the problem of ice adhesion, which is an important factor directly affecting the deicing effect. The prior art also discloses the problem of enhancing the durability of super-slippery surfaces through structural design, but fundamentally, the process of water droplets contacting and sliding off the lubricating fluid will continuously take away the lubricating fluid. The disclosed technology can only delay the failure, but cannot fundamentally solve the problem of super-slippery surface failure caused by the loss of lubricating fluid.
[0005] In summary, there is an urgent need to propose an effective solution to the problems that super-hydrophobic surfaces are difficult to remove ice and super-slippery surfaces are prone to loss and failure of lubricating fluids. Summary of the invention
[0006] Technical issues to be solved:
[0007] In order to avoid the shortcomings of the prior art, the present invention provides an anti-icing-ice-repelling composite surface and a preparation method thereof, wherein the surface is coupled with two microstructures of super-hydrophobic / lubricating fluid and hydrophobic / lubricating fluid, and the super-hydrophobic / lubricating fluid is not wetted by the lubricating fluid, while the hydrophobic / lubricating fluid is completely wrapped by the lubricating fluid, so that the surface can have both super-hydrophobic and super-slip anti-icing / ice-repelling properties, that is, it can have the excellent anti-icing performance of the super-hydrophobic surface, and can also repel ice like a super-slippery surface after the surface is frozen, making it easier to remove ice. The present invention solves the anti-icing technology that cannot be achieved by the prior art in a practical sense.
[0008] The technical solution of the present invention is: an anti-icing-icephobic composite surface, comprising a porous material substrate and a super-hydrophobic / lubricating fluid top microstructure and a hydrophobic / lubricating fluid internal microstructure coupled to the surface thereof, wherein the surface of the hydrophobic / lubricating fluid internal microstructure is injected with a lubricating fluid;
[0009] The super-hydrophobic / lubricating fluid top microstructure is located on the surface of several columns arranged in an array on a porous material substrate, and is a super-hydrophobic / lubricating fluid surface, that is, it has super-phobic properties to both water and lubricating fluid; the hydrophobic / lubricating fluid internal microstructure is also arranged in an array and surrounds the root of each column, and its surface is a hydrophobic / lubricating fluid surface, that is, it has lubricating fluid and hydrophobic properties.
[0010] A further technical solution of the present invention is that the particle diameter of the porous material used in the porous material substrate is between 0.1 and 20 microns.
[0011] A further technical solution of the present invention is: the surface of the top microstructure of the super-hydrophobic / super-lubricating fluid is a three-level composite microstructure, which is a composite structure of 20 micron, 500 nanometer and 10 nanometer microstructures from bottom to top, which can ensure the characteristics of super-hydrophobic and super-lubricating fluids.
[0012] A further technical solution of the present invention is: the columnar height of the super hydrophobic / lubricophobic fluid top microstructure is 30-60 microns, the size between adjacent columns is between 1 micron and 500 microns; the characteristic size of the columnar body is between 500 nanometers and 1000 microns.
[0013] A method for preparing an anti-icing-ice-repelling composite surface, the specific steps are as follows:
[0014] Selecting a porous material substrate, and cleaning and drying the surface thereof;
[0015] preparing a low surface energy treatment solution;
[0016] The particles for preparing the multi-level composite microstructure are subjected to low surface energy treatment by using a low surface energy treatment solution;
[0017] Composite microstructure coatings of superhydrophobic and superlubricating fluids are prepared by using particles treated with low surface energy;
[0018] The composite microstructure coating is sprayed on the surface of a porous material substrate, and the composite nanoscale microstructure in the coating is coupled with the microscale microstructure on the surface of the porous substrate to form a three-level composite microstructure surface with 10 nanometers, 500 nanometers and 20 micrometers, that is, a super hydrophobic / lubricating fluid top microstructure is obtained;
[0019] The generation area of the internal microstructure of the hydrophobic / lubricating fluid is prepared by removing materials;
[0020] The porous material substrate after material removal is subjected to low surface energy treatment to generate a hydrophobic / lubricating fluid internal microstructure in the material removal area;
[0021] By injecting lubricating fluid into the surface of the microstructure inside the hydrophobic / lubricating fluid, an anti-icing-icephobic composite surface is obtained.
[0022] A further technical solution of the present invention is: the preparation method of the low surface energy treatment solution is:
[0023] Add anhydrous ethanol into a beaker and stir at room temperature;
[0024] gradually adding perfluorodecyltriethoxysilane and continuously stirring for 10 minutes to obtain a perfluorodecyltriethoxysilane ethanol low surface energy treatment solution;
[0025] Wherein, the product ratio of perfluorodecyltriethoxysilane and anhydrous ethanol is 2:100.
[0026] A further technical solution of the present invention is: the method of using a low surface energy treatment solution to perform low surface energy treatment on particles for preparing a multi-level composite microstructure is:
[0027] 300-500 nanometer diameter silica nanoparticles, 10-50 nanometer diameter silica nanoparticles and carbon nanotubes are slowly added to the low surface energy treatment solution at a mass ratio of 3.5:2.2:2, and stirred for 3-5 hours;
[0028] The solution obtained after stirring is filtered using filter paper to filter out the silicon dioxide nanoparticles with a diameter of 300-500 nanometers, the silicon dioxide nanoparticles with a diameter of 10-50 nanometers and the carbon nanotubes, and the surface moisture is dried;
[0029] The drying was continued at 120° C. for 3 hours to allow the surface perfluorodecyltriethoxysilane to be completely grafted onto the surface of the nanoparticles, thereby obtaining a mixed powder.
[0030] A further technical solution of the present invention is: the method for preparing the composite microstructure coating of super-hydrophobic and super-lubricating fluid is:
[0031] Add ethanol as solvent into the beaker and keep stirring at room temperature;
[0032] Add the low surface energy treated mixed powder into the ethanol solution and stir evenly;
[0033] gradually adding polytetrafluoroethylene emulsion and stirring evenly to obtain a mixed solution;
[0034] The uniformly mixed solution is placed in an ultrasonic bath for ultrasonic treatment for 30 minutes to obtain a composite microstructure coating with uniformly mixed particles;
[0035] Among them, the mass ratio of polytetrafluoroethylene emulsion, 300-500 nanometer diameter silica nanoparticles, 10-50 nanometer diameter silica nanoparticles, carbon nanotubes, and anhydrous ethanol is 3.6:3.5:2.2:2:10.
[0036] A further technical solution of the present invention is: the preparation method of the super hydrophobic / lubricating fluid top microstructure is:
[0037] Spraying the composite microstructure coating onto the surface of the porous material substrate with a thickness of less than 20 microns;
[0038] The surface of the porous material substrate after spraying the coating was placed in an oven, and the temperature was set to rise from room temperature to 350 degrees Celsius for 3 hours, and then maintained at 350 degrees Celsius for 10 minutes and then slowly dropped to room temperature;
[0039] The composite nanoscale microstructure in the coating is coupled with the microscale microstructure on the porous substrate surface to form a three-level composite microstructure surface with 10 nanometers, 500 nanometers and 20 micrometers, which can ensure the characteristics of superhydrophobic and superlubricating fluids.
[0040] A further technical solution of the present invention is: the preparation method of the internal microstructure of the hydrophobic / lubricating fluid is:
[0041] The porous material substrate with the composite microstructure surface is subjected to material removal processing, wherein the concave part after the material is removed is the generation area of the internal microstructure of the hydrophobic / lubricating fluid, and the part without material removal is a number of columns with super hydrophobic / lubricating fluid top microstructures, which are arranged in a periodic array;
[0042] The surface of the porous material substrate after material removal is treated with low surface energy; first, perfluorodecyltriethoxysilane is dropped into a culture dish, and the surface of the porous material substrate after material removal is placed in the culture dish together; then, the culture dish is placed in an oven and heated to 80 degrees Celsius, and then quickly taken out and placed in a vacuum kettle for vacuum treatment for 1 hour; then, it is taken out and continued to be heated in the oven at 120 degrees Celsius for 3 hours, and taken out after heating is completed, so as to obtain the internal microstructure of the hydrophobic / lubricating fluid.
[0043] Beneficial Effects
[0044] The beneficial effect of the present invention is that the present invention couples the two microstructures of super-hydrophobic / lubricating fluid and hydrophobic / lubricating fluid, so that the surface of the porous material substrate has the characteristics of super-hydrophobic / lubricating fluid microstructure and hydrophobic / lubricating fluid microstructure at the same time, so that the super-hydrophobic surface can achieve the anti-icing property, and even if the surface is frozen, the ice can be easily removed. The surface structure of the present invention can greatly promote the progress of modern anti-icing surface technology. The specific advantages are as follows:
[0045] 1. The present invention creatively proposes an anti-icing-ice-repellent composite surface that combines a super-hydrophobic surface and a super-slippery surface. This surface has excellent super-hydrophobic properties (average contact angle greater than 150°) and can significantly reduce the adhesion of ice after the surface is frozen (so that the ice adhesion can be reduced to below 85 kPa).
[0046] 2. The super-hydrophobic layer of the top layer of the surface of the present invention can play a super-hydrophobic role. When the surface encounters water droplets, the super-hydrophobic property can make it bounce away quickly without adhering to the surface, preventing large-scale icing; At the same time, because the water droplets will be quickly bounced away without contacting the lubricating fluid inside the microstructure, the loss of lubricating fluid caused by the water droplets taking the lubricating fluid away is also avoided. Unlike super-hydrophobic, when the surface is washed for a long time and many times, defects appear on the super-hydrophobic surface, causing the hydrophobic performance to weaken, causing the water droplets to adhere to the accumulation of ice, or when encountering water vapor condensation and freezing on the surface, the lubricating fluid in the groove of the super-hydrophobic structure will hinder the ice crystals from being embedded inside the super-hydrophobic structure, preventing the microstructure and the surface microstructure from forming a mechanical interlock, thereby greatly reducing the adhesion of ice. With the increase of ice accumulation, ice accumulation will also fall off from the surface under the action of its own gravity. In addition, since the lubricating fluid is inside the groove of the super-hydrophobic surface, this also makes the lubricating fluid less likely to lose, thereby greatly increasing the effective service life of the surface.
[0047] 3. The preparation method of the present invention specifically defines the raw materials and particle sizes for preparing a super hydrophobic / lubricating fluid top microstructure that can repel both lubricating fluids and water, wherein the mass ratio of polytetrafluoroethylene emulsion, 300-500 nanometer diameter silica nanoparticles, 10-50 nanometer diameter silica nanoparticles, carbon nanotubes, and anhydrous ethanol reaches 3.6:3.5:2.2:2:10. Under this mass ratio, the number of particles of each size is moderate, and gravity and surface tension are balanced, which can ensure that small-sized nano-scale silica particles, carbon nanotubes and polytetrafluoroethylene particles are attached to the surface of large-sized particles, so that the surface of large-sized particles is completely covered by small-sized particles without forming large-area accumulation, and finally a more uniform, more clearly structured, and larger surface area three-level composite microstructure surface with 10 nanometers, 500 nanometers and 20 micrometers is formed. After low surface energy treatment, the complex three-level microstructure will more stably bind the air in the microstructure cavity, thereby preventing the lubricating fluid and water from penetrating into the microstructure, thereby ensuring superhydrophobicity while obtaining better superphobic lubricating fluid properties.
[0048] The surface anti-icing and ice-repelling performance mentioned in the present invention is strong, and the processing method is highly applicable. It can be processed on a large area on the surface of different metal materials or polymer materials, and is expected to solve the difficult problems of anti-icing and ice-repelling engineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a structural illustration of an anti-icing-ice-repelling composite surface in an embodiment of the present invention;
[0050] Figure 2 A top view of a square columnar microstructure according to an embodiment of the present invention;
[0051] Figure 3 A top view of a cylindrical microstructure in an embodiment of the present invention;
[0052] Figure 4 This is a macroscopic large-scale sample diagram of a microstructure processing object in an embodiment of the present invention;
[0053] Figure 5 This is a microscopic enlarged sample diagram of the microstructure in the embodiment of the present invention;
[0054] Figure 6 This is a measurement diagram of super hydrophobicity of the microstructure surface in an embodiment of the present invention;
[0055] Figure 7 This is a graph showing the ice adhesion test results in an embodiment of the present invention;
[0056] Figure 8 Figure 1 of Example 1 of the present invention shows (a) surface and contact angle and (b) adhesion test results;
[0057] Fig. 9 Figure 2 of Example 2 of the present invention shows (a) surface and contact angle and (b) adhesion test results;
[0058] Explanation of the reference numerals: 1. porous material substrate, 2. super hydrophobic / lubricating fluid top microstructure, 3. hydrophobic / lubricating fluid internal microstructure, 4. lubricating fluid. DETAILED DESCRIPTION
[0059] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0060] Based on the problems in the prior art that super-hydrophobic surfaces are difficult to remove after ice is formed, and the lubricating fluid on super-slippery surfaces is easy to lose and become ineffective, the present invention provides an anti-icing-ice-repelling composite surface. Figure 1 As shown, it includes a porous material substrate 1, a super-hydrophobic / lubricating fluid top microstructure 2, a hydrophobic / lubricating fluid internal microstructure 3 and a lubricating fluid 4; the super-hydrophobic / lubricating fluid top microstructure 2 is located on the surface of a plurality of columns arranged in an array on the porous material substrate 1, and is a super-hydrophobic / lubricating fluid surface, that is, it has super-phobic properties to both water and lubricating fluid; the hydrophobic / lubricating fluid internal microstructure 3 is also arranged in an array and surrounds the root of each column, and its surface is a hydrophobic / lubricating fluid surface, that is, it has lubricating fluid and hydrophobic properties.
[0061] Among them, refer to Figure 2 and Figure 3 As shown, the porous material substrate 1 is the carrier for all microstructure processing; the super-hydrophobic / lubricating fluid top microstructure 2 is the outermost microstructure in contact with water droplets and ice after etching, and has super-phobic properties to both water and lubricating fluids, so that neither water droplets nor super-slippery fluids can wet its surface; the hydrophobic / lubricating fluid internal microstructure 3 is an inner concave structure etched on the surface of the porous material substrate 1, and the surface has lubricating fluid and hydrophobic properties, and can be wetted by the lubricating fluid (the contact angle of the lubricating fluid on its surface is less than 90°) but cannot be wetted by water droplets (the contact angle of the water droplets on its surface is greater than 90°); the lubricating fluid 4 is inside the hydrophobic / lubricating fluid microstructure 3, and does not wet the super-hydrophobic / lubricating fluid top microstructure 2; it should be noted that the porous material substrate 1 can use different materials according to different usage scenarios, and the particle diameter of the porous material is between 0.1-20 microns; the freezing temperature of the lubricating fluid 4 should be lower than the lowest temperature of the use environment (generally, the freezing temperature of the lubricating fluid should be lower than -20°C).
[0062] The anti-icing / ice-repelling principle of the anti-icing-ice-repelling composite surface: the super-hydrophobic layer on the top layer of the surface can play a super-hydrophobic role. When the surface encounters water droplets, the super-hydrophobic property can make it bounce away quickly without adhering to the surface, preventing large-scale icing; at the same time, because the water droplets will be quickly bounced away without contacting the lubricating fluid inside the microstructure, the loss of lubricating fluid caused by the water droplets taking the lubricating fluid away is also avoided. Unlike super-hydrophobicity, when the surface is washed for a long time and many times, defects appear on the super-hydrophobic surface, causing the hydrophobic performance to weaken, causing water droplets to adhere to the accumulation of ice, or when encountering water vapor condensation and freezing on the surface, the lubricating fluid in the groove of the super-hydrophobic structure will hinder the ice crystals from being embedded in the super-hydrophobic structure, preventing the microstructure and the surface microstructure from forming a mechanical interlock, thereby greatly reducing the adhesion of ice. With the increase of ice accumulation, the ice accumulation will also fall off the surface under the action of its own gravity. In addition, since the lubricating fluid is inside the groove of the super-hydrophobic surface, this also makes the lubricating fluid less likely to be lost, thereby greatly increasing the effective service life of the surface.
[0063] The present invention provides a method for preparing an anti-icing-ice-phobic composite surface with superphobic-superslip properties, and the specific steps are as follows:
[0064] Step 1: Prepare the material substrate: Take a porous material substrate of appropriate size, first use acetone ultrasonic cleaning for 30 minutes, then use anhydrous ethanol ultrasonic cleaning for 30 minutes, and finally use deionized water ultrasonic cleaning for 30 minutes, put it into a high-temperature drying oven at 120 degrees Celsius and dry it for 2 hours for use, to obtain an impurity-free substrate surface.
[0065] Step 2: Selecting raw materials for preparing a super hydrophobic / lubricating fluid top microstructure 2 that can repel both lubricating fluid and water: taking silica nanoparticles with a diameter of 10-50 nanometers and a diameter of 300-500 nanometers, polytetrafluoroethylene emulsion (mass fraction 60%), perfluorodecyl triethoxysilane, carbon nanotubes and anhydrous ethanol for use;
[0066] Step 3: Prepare a low surface energy treatment solution: Take perfluorodecyltriethoxysilane and anhydrous ethanol in a volume ratio of 2:100, first add anhydrous ethanol into a beaker, place the beaker on a magnetic stirrer and start stirring at room temperature, then gradually add perfluorodecyltriethoxysilane and continue stirring for 10 minutes to obtain a perfluorodecyltriethoxysilane ethanol low surface energy treatment solution.
[0067] Step 4: Treat the particles with low surface energy: Take 300-500 nanometer diameter silica nanoparticles, 10-50 nanometer diameter silica nanoparticles and carbon nanotubes in a mass ratio of 3.5:2.2:2, and slowly add them to the solution prepared in step 3, and continue stirring for 3-5 hours; carbon nanotubes, silica nanoparticles with a diameter of 10-50 nanometers and a diameter of 300-500 nanometers are used to form a composite microstructure with a multi-level structure. It should be noted that during the stirring process, the beaker mouth needs to be covered with plastic wrap to prevent the volatilization of the liquid components.
[0068] Step 5: Filter out the 300-500 nanometer diameter silica nanoparticles, 10-50 nanometer diameter silica nanoparticles and carbon nanotubes in the beaker of step 4 through filter paper, and then put the filtered mixed powder into an oven; first dry it at 80°C for 3 hours to slowly dry the anhydrous ethanol on the surface, and then dry it at 120°C for 3 hours to completely graft the surface perfluorodecyltriethoxysilane to the surface of the nanoparticles to obtain a mixed powder.
[0069] Step 6: Prepare a composite microstructure coating that is both lubricating fluid-repellent and hydrophobic: Take out the above-mentioned dried powder for use, and take polytetrafluoroethylene emulsion and anhydrous ethanol, so that the mass ratio of polytetrafluoroethylene emulsion, 300-500 nanometer diameter silica nanoparticles, 10-50 nanometer diameter silica nanoparticles, carbon nanotubes, and anhydrous ethanol reaches 3.6:3.5:2.2:2:10.
[0070] First, add ethanol as a solvent into a beaker and stir continuously with a magnetic stirrer, then add the mixed powder prepared in step 5 into the ethanol solution, cover the beaker with plastic wrap, and stir at room temperature for 3 to 5 hours until it is uniformly stirred. Then gradually add the polytetrafluoroethylene emulsion to the above-mentioned uniform solution, and continue to stir at room temperature for 3 to 5 hours until it is uniformly stirred. Finally, place the uniformly mixed solution in an ultrasonic bath for ultrasonic treatment for 30 minutes to ensure that the particles are more uniformly mixed, that is, a composite microstructure coating with uniformly mixed particles is obtained.
[0071] It has been proven that this ratio can ensure that small-sized nano-sized silica particles, carbon nanotubes and polytetrafluoroethylene particles are attached to the surface of large-sized particles to form a multi-level composite microstructure.
[0072] Step 7: Spray the coating to form a coating on the surface of the substrate: Spray the solution prepared in step 6 onto the surface of the porous material substrate prepared in step 1, and keep the spraying thickness less than 20 microns.
[0073] Step 8: Dry the coating and enhance the adhesion of the coating: Place the substrate surface after spraying the coating in an oven, set the temperature to rise from room temperature to 350 degrees Celsius for 3 hours, maintain it at 350 degrees Celsius for 10 minutes, and then slowly cool it to room temperature; this temperature will cause the polytetrafluoroethylene particles in the polytetrafluoroethylene emulsion to begin to melt and become a fluid state, thereby firmly bonding the above-mentioned nanoparticles and the substrate surface together, and heating for 10 minutes to ensure that the polytetrafluoroethylene particles will not flow too much into the porous microstructure substrate after melting. At this point, the composite nanoscale microstructure in the coating is coupled with the micron-scale microstructure on the surface of the porous substrate, forming a three-level composite microstructure surface with 10 nanometers, 500 nanometers and 20 micrometers, which can ensure the characteristics of super-hydrophobic and super-repellent lubricating fluids.
[0074] Step 9: Preparation of hydrophobic / lubricating fluid internal microstructure 3: Take the prepared surface out of the oven, and use a material removal processing method (such as laser processing, mechanical processing, etc.) to process the surface of the substrate material. Figure 2 The microstructure shown in the figure is a square, and it can also be processed into other shapes such as a circle, an ellipse, a polygon, etc., where the shaded part is the removed material part, and the thickness of the removed material is about 30 to 60 microns (the coating prepared in steps 7 and 8 is completely removed from the substrate surface). The inter-column spacing L1 and L2 are between 1 micron and 500 microns, and the column feature size L is between 500 nanometers and 1000 microns.
[0075] Step 10: Treat the substrate surface with low surface energy: Take 5 microliters of perfluorodecyltriethoxysilane and drop it into a culture dish, put the surface processed in step 9 into the culture dish, then put the culture dish into an oven and heat it to 80 degrees Celsius, quickly take it out and put it into a vacuum kettle for vacuum treatment for 1 hour, then take it out and continue to heat it in the oven at 120 degrees Celsius for 3 hours, and take it out after heating is completed.
[0076] Step 11: Infuse lubricating fluid 4: Take out the surface processed in step 10 and immerse it in lubricating fluid. Soak it for 5 minutes and then take it out. Figure 1 The surface microstructure shown.
[0077] The above technical solution is further explained below with reference to examples:
[0078] Embodiment 1:
[0079] This embodiment is a titanium plate porous material-based anti-icing-ice-repellent composite surface and a preparation method, and the specific steps are as follows:
[0080] Step 1: Prepare a 40cm*40cm titanium plate porous material substrate, first use acetone ultrasonic cleaning for 30 minutes, then use anhydrous ethanol ultrasonic cleaning for 30 minutes, and finally use deionized water ultrasonic cleaning for 30 minutes, then put it into a high-temperature drying oven at 120 degrees Celsius for 2 hours for use.
[0081] Step 2: Prepare silicon dioxide nanoparticles with a diameter of 50 nanometers and a diameter of 500 nanometers, polytetrafluoroethylene emulsion (mass fraction 60%), perfluorodecyltriethoxysilane, carbon nanotubes and anhydrous ethanol for later use.
[0082] Step 3: Take 1 ml of perfluorodecyltriethoxysilane and 100 ml of anhydrous ethanol, first add the anhydrous ethanol into a beaker, place the beaker on a magnetic stirrer and start stirring at room temperature, then gradually add perfluorodecyltriethoxysilane and continue stirring for 10 minutes.
[0083] Step 4: Take 56 grams of 500-nanometer-diameter silica nanoparticles, 35.2 grams of 50-nanometer-diameter silica nanoparticles, and 32 grams of carbon nanotubes, and slowly add them to the solution prepared in step 3, and continue stirring for 3-5 hours; it should be noted that during the stirring process, the mouth of the beaker should be covered with plastic wrap to prevent the volatilization of the liquid components.
[0084] Step 5: Filter out the nanometer-diameter silica nanoparticles and carbon nanotubes in the beaker of step 4 through filter paper, and then put the filtered mixed powder into an oven and dry it at 80° C. and 120° C. for 3 hours respectively until it is completely dry.
[0085] Step 6: Take out the above dried powder for use, and take 57.6 grams of polytetrafluoroethylene emulsion and 160 grams of anhydrous ethanol. First, add ethanol to a beaker and stir continuously with a magnetic stirrer. Then add the mixed powder prepared in step 5 to the ethanol solution, cover the beaker with plastic wrap, and stir at room temperature for 3 to 5 hours until it is uniform. Then gradually add polytetrafluoroethylene emulsion to the above uniform solution, and continue to stir at room temperature for 3 to 5 hours until it is uniform. Finally, put the uniform mixed solution into an ultrasonic tank for ultrasonic treatment for 30 minutes.
[0086] Step 7: Spray the solution prepared in step 6 onto the surface of the porous material substrate prepared in step 1, and keep the spraying thickness less than 20 microns.
[0087] Step 8: Place the substrate surface after spraying the coating in an oven, set the temperature to rise from room temperature to 350 degrees Celsius in 3 hours, maintain at 350 degrees Celsius for 10 minutes, and then slowly cool it down to room temperature.
[0088] Step 9: Take the prepared surface out of the oven and use laser etching to process the surface of the substrate material. Figure 2 The square microstructure shown, where the shaded part is the removed material part, the thickness of the removed material is 30 microns, where the inter-column spacing L1 and L2 are 100 microns, and the column feature size L is 100 microns.
[0089] Step 10: Take 5 microliters of perfluorodecyltriethoxysilane and drop it into the culture dish, put the surface processed in step 9 into the culture dish, then put the culture dish into the oven and heat it to 80 degrees Celsius, quickly take it out and put it into a vacuum kettle for vacuum treatment for 1 hour, then take it out and continue to heat it in the oven at 120 degrees Celsius for 3 hours, and take it out after heating is completed.
[0090] Step 11: Take out the surface processed in step 10 and immerse it in a lubricating fluid with a viscosity of 50 mPa.s. Soak it for 5 minutes and then take it out. At this time, an anti-icing and ice-repellent microstructure surface can be obtained.
[0091] The processed microstructure surface is Figure 8 As shown, the surface has excellent superhydrophobic properties, and the adhesion force of ice can be maintained below 80KPa under multiple measurements.
[0092] Embodiment 2:
[0093] This embodiment is an aluminum-based anti-icing-ice-repellent composite surface with super-phobic-super-slip properties and a preparation method, and the specific steps are as follows:
[0094] Step 1: Prepare a 40cm*40cm aluminum-based porous material substrate, first use acetone ultrasonic cleaning for 30 minutes, then use anhydrous ethanol ultrasonic cleaning for 30 minutes, and finally use deionized water ultrasonic cleaning for 30 minutes, then put it into a high-temperature drying oven at 120 degrees Celsius for 2 hours for use.
[0095] Step 2: Prepare silicon dioxide nanoparticles with a diameter of 50 nanometers and a diameter of 500 nanometers, polytetrafluoroethylene emulsion (mass fraction 60%), perfluorodecyltriethoxysilane, carbon nanotubes and anhydrous ethanol for later use.
[0096] Step 3: Take 1 ml of perfluorodecyltriethoxysilane and 100 ml of anhydrous ethanol, first add the anhydrous ethanol into a beaker, place the beaker on a magnetic stirrer and start stirring at room temperature, then gradually add perfluorodecyltriethoxysilane and continue stirring for 10 minutes.
[0097] Step 4: Take 56 grams of 500-nanometer-diameter silica nanoparticles, 35.2 grams of 50-nanometer-diameter silica nanoparticles, and 32 grams of carbon nanotubes, and slowly add them to the solution prepared in step 3, and continue stirring for 3-5 hours; it should be noted that during the stirring process, the mouth of the beaker should be covered with plastic wrap to prevent the volatilization of the liquid components.
[0098] Step 5: Filter out the nanometer-diameter silica nanoparticles and carbon nanotubes in the beaker of step 4 through filter paper, and then put the filtered mixed powder into an oven and dry it at 80° C. and 120° C. for 3 hours respectively until it is completely dry.
[0099] Step 6: Take out the above dried powder for use, and take 57.6 grams of polytetrafluoroethylene emulsion and 160 grams of anhydrous ethanol. First, add ethanol to a beaker and stir continuously with a magnetic stirrer. Then add the mixed powder prepared in step 5 to the ethanol solution, cover the beaker with plastic wrap, and stir at room temperature for 3 to 5 hours until it is uniform. Then gradually add polytetrafluoroethylene emulsion to the above uniform solution, and continue to stir at room temperature for 3 to 5 hours until it is uniform. Finally, put the uniform mixed solution into an ultrasonic tank for ultrasonic treatment for 30 minutes.
[0100] Step 7: Spray the solution prepared in step 6 onto the surface of the porous material substrate prepared in step 1, and keep the spraying thickness less than 20 microns.
[0101] Step 8: Place the substrate surface after spraying the coating in an oven, set the temperature to rise from room temperature to 350 degrees Celsius in 3 hours, maintain at 350 degrees Celsius for 10 minutes, and then slowly cool it down to room temperature.
[0102] Step 9: Take the prepared surface out of the oven and use laser etching to process the surface of the substrate material. Figure 3 The circular microstructure shown, where the shaded part is the removed material part, the thickness of the removed material is 40 microns, where the inter-column spacing L1 and L2 are 100 microns, and the column feature size L is 100 microns.
[0103] Step 10: Take 5 microliters of perfluorodecyltriethoxysilane and drop it into the culture dish, put the surface processed in step 9 into the culture dish, then put the culture dish into the oven and heat it to 80 degrees Celsius, quickly take it out and put it into a vacuum kettle for vacuum treatment for 1 hour, then take it out and continue to heat it in the oven at 120 degrees Celsius for 3 hours, and take it out after heating is completed.
[0104] Step 11: Take out the surface processed in step 10 and immerse it in a lubricating fluid with a viscosity of 50 mPa.s. Soak it for 5 minutes and then take it out. At this time, an anti-icing and ice-repellent microstructure surface can be obtained.
[0105] The processed microstructure surface is Fig. 9 As shown, the surface has excellent superhydrophobic properties, and the adhesion of ice can be maintained below 80KPa under multiple measurements.
[0106] It should be noted that: (1) the embodiments provided in the present invention are an expansion and extension of the ideas of the present invention and are not intended to limit the content of the present invention; (2) all preparations in any manner to implement the ideas provided by the present invention, namely: the portion of the top of the groove that directly contacts water or ice (or the microstructure protrusion, the top microstructure portion) has an oleophobic and hydrophobic property, the interior of the groove (the microstructure recessed portion, the bottom microstructure portion, or the rest of the portion except the top microstructure) has a lubricating fluid-philic and hydrophobic property, and when the lubricating fluid is injected into the interior of the groove, the top of the groove still has an oleophobic surface, all fall within the protection scope of the present invention.
[0107] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. An anti-icing-ice-repelling composite surface, characterized in that: It comprises a porous material substrate and a super hydrophobic / lubricating fluid top microstructure coupled to the surface thereof and a hydrophobic / lubricating fluid internal microstructure, wherein the surface of the hydrophobic / lubricating fluid internal microstructure is injected with a lubricating fluid; The super-hydrophobic / lubricating fluid top microstructure is located on the surface of several columns arranged in an array on a porous material substrate, and is a super-hydrophobic / lubricating fluid surface, that is, it has super-phobic properties to both water and lubricating fluid; the hydrophobic / lubricating fluid internal microstructure is also arranged in an array and surrounds the root of each column, and its surface is a hydrophobic / lubricating fluid surface, that is, it has lubricating fluid and hydrophobic properties.
2. The anti-icing-ice-repellent composite surface according to claim 1, characterized in that: The particle diameter of the porous material used in the porous material substrate is between 0.1 and 20 microns.
3. The anti-icing-ice-repellent composite surface according to claim 1, characterized in that: The surface of the super-hydrophobic / super-lubricating fluid top microstructure is a three-level composite microstructure, which is a composite structure of 20 micron-level, 500 nanometer-level, and 10 nanometer-level microstructures from bottom to top, which can ensure the characteristics of super-hydrophobic and super-lubricating fluids.
4. The anti-icing-ice-phobic composite surface according to claim 1, characterized in that: The columnar height of the super hydrophobic / lubricating fluid top microstructure is 30-60 microns, the size between adjacent columns is between 1 micron and 500 microns; the characteristic size of the columnar body is between 500 nanometers and 1000 microns.
5. A method for preparing the anti-icing-icephobic composite surface according to any one of claims 1 to 4, characterized in that The specific steps are as follows: Selecting a porous material substrate, and cleaning and drying the surface thereof; preparing a low surface energy treatment solution; The particles for preparing the multi-level composite microstructure are subjected to low surface energy treatment using a low surface energy treatment solution; Composite microstructure coatings of superhydrophobic and superlubricating fluids are prepared by using particles treated with low surface energy; The composite microstructure coating is sprayed on the surface of a porous material substrate, and the composite nanoscale microstructure in the coating is coupled with the microscale microstructure on the surface of the porous substrate to form a three-level composite microstructure surface with 10 nanometers, 500 nanometers and 20 micrometers, that is, a super hydrophobic / lubricating fluid top microstructure is obtained; The generation area of the internal microstructure of the hydrophobic / lubricating fluid is prepared by removing materials; The porous material substrate after material removal is subjected to low surface energy treatment to generate a hydrophobic / lubricating fluid internal microstructure in the material removal area; By injecting lubricating fluid into the surface of the microstructure inside the hydrophobic / lubricating fluid, an anti-icing-icephobic composite surface is obtained.
6. The method for preparing an anti-icing-icephobic composite surface according to claim 5, characterized in that: The preparation method of the low surface energy treatment solution is: Add anhydrous ethanol into a beaker and stir at room temperature; gradually adding perfluorodecyltriethoxysilane and continuously stirring for 10 minutes to obtain a perfluorodecyltriethoxysilane ethanol low surface energy treatment solution; Wherein, the product ratio of perfluorodecyltriethoxysilane and anhydrous ethanol is 2:
100.
7. The method for preparing an anti-icing-ice-phobic composite surface according to claim 6, characterized in that: The method of using a low surface energy treatment solution to perform low surface energy treatment on particles for preparing a multi-level composite microstructure is: 300-500 nanometer diameter silica nanoparticles, 10-50 nanometer diameter silica nanoparticles and carbon nanotubes are slowly added to the low surface energy treatment solution at a mass ratio of 3.5:2.2:2, and stirred for 3-5 hours; The solution obtained after stirring is filtered using filter paper to filter out the silicon dioxide nanoparticles with a diameter of 300-500 nanometers, the silicon dioxide nanoparticles with a diameter of 10-50 nanometers and the carbon nanotubes, and the surface moisture is dried; The drying was continued at 120° C. for 3 hours to allow the surface perfluorodecyltriethoxysilane to be completely grafted onto the surface of the nanoparticles, thereby obtaining a mixed powder.
8. The method for preparing an anti-icing-ice-phobic composite surface according to claim 7, characterized in that: The method for preparing the composite microstructure coating of super-hydrophobic and super-lubricating fluid is: Add ethanol as solvent into the beaker and keep stirring at room temperature; Add the low surface energy treated mixed powder into the ethanol solution and stir evenly; gradually adding polytetrafluoroethylene emulsion and stirring evenly to obtain a mixed solution; The uniformly mixed solution is placed in an ultrasonic bath for ultrasonic treatment for 30 minutes to obtain a composite microstructure coating with uniformly mixed particles; Among them, the mass ratio of polytetrafluoroethylene emulsion, 300-500 nanometer diameter silica nanoparticles, 10-50 nanometer diameter silica nanoparticles, carbon nanotubes, and anhydrous ethanol is 3.6:3.5:2.2:2:
10.
9. The method for preparing an anti-icing-icephobic composite surface according to claim 8, characterized in that: The preparation method of the super hydrophobic / lubricating fluid top microstructure is: Spraying the composite microstructure coating onto the surface of the porous material substrate with a thickness of less than 20 microns; The surface of the porous material substrate after spraying the coating was placed in an oven, and the temperature was set to rise from room temperature to 350 degrees Celsius for 3 hours, and then maintained at 350 degrees Celsius for 10 minutes and then slowly dropped to room temperature; The composite nanoscale microstructure in the coating is coupled with the microscale microstructure on the porous substrate surface to form a three-level composite microstructure surface with 10 nanometers, 500 nanometers and 20 micrometers, which can ensure the characteristics of superhydrophobic and superlubricating fluids.
10. The method for preparing an anti-icing-icephobic composite surface according to claim 9, characterized in that: The preparation method of the internal microstructure of the hydrophobic / lubricating fluid is as follows: The porous material substrate with the composite microstructure surface is subjected to material removal processing, wherein the concave part after the material is removed is the generation area of the internal microstructure of the hydrophobic / lubricating fluid, and the part without material removal is a number of columns with super hydrophobic / lubricating fluid top microstructures, which are arranged in a periodic array; The surface of the porous material substrate after material removal is treated with low surface energy; first, perfluorodecyltriethoxysilane is dropped into a culture dish, and the surface of the porous material substrate after material removal is placed in the culture dish together; then, the culture dish is placed in an oven and heated to 80 degrees Celsius, and then quickly taken out and placed in a vacuum kettle for vacuum treatment for 1 hour; then, it is taken out and continued to be heated in the oven at 120 degrees Celsius for 3 hours, and taken out after heating is completed, so as to obtain the internal microstructure of the hydrophobic / lubricating fluid.
Citation Information
Patent Citations
Nano superhydrophobic surface used for airplane antifreezing and deicing and preparation method thereof
CN101704410A
Super-hydrophobic material and preparation method thereof
CN105969174A
Super-hydrophobic-lubricating composite anti-icing coating with porous structure and preparation method thereof
CN111303738A
Super-hydrophilic water-absorbing material and preparation method of durable wetting gradient surface
CN116217792A
Mechanical multiple torque damping device for a horizontal spindle
KR1020230014052A
Cited By
Polar region ship anti-icing coating capable of adjusting ice adhesive force and preparation method
CN119912873A
An anti-icing coating for polar ships with adjustable ice adhesion and its preparation method
CN119912873B
Preparation method of carbon nanotube cluster micro-nano composite photo-thermal super-hydrophobic anti-icing coating
CN119955378A
Nano aramid fiber reinforced ice-dredging composite material as well as preparation method and application thereof
CN121628574A